Management of tuberculosis patients by grass root level practitioners - Mangal, Shweta; Belani, Preeti (International Journal Of Community Medicine And Public Health, 2017)
Background: The tuberculosis bacteria are the top most infectious killing agents in the world. 9.6 million is the number of people that developed tuberculosis globally in the year 2014. The objective was to evaluate the management of Tuberculosis patients by grass root level practitioners as a one of the cause behind slow progress in TB control and increasing resistance to anti-TB drugs. Methods: Cross sectional, observational study with pretested, semi structured proforma with open and close ended questions. Results: Very few practitioners are updated about the renewed RNTCP guidelines. Only 25.58% know about cough for more than two weeks as a prime symptom, and 48.71% know that two sputum samples have to be taken for diagnosis. Most of them are not taking the recommended morning and spot samples. There is an overdependence on X-Ray for diagnosis and follow up. 64% of the practitioners do not notify the DTC. Only 22% knew of the two categories of TB patients according to the RNTCP guidelines. Supervision of treatment and intermittent dosing, as advised by RNTCP, are not strictly followed by most practitioners, and only 20% were doing a sputum examination at the end of two months and 6 months. Overtreatment is commonly seen. Awareness about applicability of DOTS on children and contraindication of Streptomycin in pregnancy is inadequate. Conclusion: The knowledge and practice of the grass root level practitioners is significantly below mark and may contribute to the static or slow decreasing burden of TB, and increasing drug resistance. The practitioners should be registered, adequately trained, and properly equipped to deal with the TB patients, to avoid the emergence of newer drug resistant tubercular cases.